PENINGKATAN HASIL BELAJAR BIOLOGI SISWA KELAS IX SMP NEGERI 2 BAJENG KABUPATEN GOWA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD PADA KONSEP PERTUMBUHAN DAN PERKEMBANGAN - Mariati, .; Kaseng, Ernawati Saharuddin (Fakultas MIPA UNM, 2009)
This research was classroom action research that have purpose to know increating of biology study result. Subject in this research is the ninth class, the amount of thirty five (35) students. This research is carried out during two cycle the result of research give description that there is taught by learning method of the type STAD cooperative in SMP 2 Bajeng of Gowa regency. Keywords: biology study result, cooperative learning, STAD